2019
DOI: 10.1007/s13311-019-00790-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Therapeutics for SBMA/Kennedy's Disease

Abstract: Spinal and bulbar muscular atrophy (SBMA) is a neuromuscular disease caused by a polyglutamine (polyQ) expansion in the androgen receptor (AR). Despite the fact that the monogenic cause of SBMA has been known for nearly 3 decades, there is no effective treatment for this disease, underscoring the complexity of the pathogenic mechanisms that lead to a loss of motor neurons and muscle in SBMA patients. In the current review, we provide an overview of the system-wide clinical features of SBMA, summarize the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 228 publications
0
21
0
Order By: Relevance
“…Spinal and bulbar muscular atrophy (SBMA) is a slow progressive neuromuscular disorder in which the lower motor neurons and muscles degenerate. SBMA is X-linked and therefore mainly affecting males, with some exceptions discussed in the Arnold and Merry review [11]. The symptoms include gynecomastia, testicular atrophy, and reduced fertility, all which correlate with the known function of AR as a transcription factor binding androgen hormones.…”
Section: Spinal and Bulbar Muscular Atrophy/kennedy's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Spinal and bulbar muscular atrophy (SBMA) is a slow progressive neuromuscular disorder in which the lower motor neurons and muscles degenerate. SBMA is X-linked and therefore mainly affecting males, with some exceptions discussed in the Arnold and Merry review [11]. The symptoms include gynecomastia, testicular atrophy, and reduced fertility, all which correlate with the known function of AR as a transcription factor binding androgen hormones.…”
Section: Spinal and Bulbar Muscular Atrophy/kennedy's Diseasementioning
confidence: 99%
“…Given the known function of AR, the normal lifespan of SBMA patients, and the rapid progress in the field, it is surprising that after almost thirty years of investigation, we do not have a therapeutic treatment for this disease. Merry reviews the complexity of the underlying pathogenesis of this disorder and highlights steps that may lead to therapeutics for SBMA/Kennedy's disease [11].…”
Section: Spinal and Bulbar Muscular Atrophy/kennedy's Diseasementioning
confidence: 99%
“…The mutant AR aggregates in the nucleus of a cell and results in direct toxicity to the cell (mostly, lower motor neurons and myofibrils), which clinically results in slowly progressive adult-onset lower motor neuron damage and primary myopathy early in the course of the disease (3,4). Interestingly, myopathic changes in transgenic mouse models of SBMA were observed prior to any motor neuron degeneration, illustrating motor neuron involvement only in the later stages of SBMA (5)(6)(7). Additionally, the polyglutamine expansion causes loss of receptor activity and results in androgen insensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile onset commonly manifests itself with limb atrophy and gynecomastia between 8 to 15 years of age ( Echaniz-Laguna et al, 2005 ). Neurodegeneration in adult SBMA is mainly characterized by loss of motor neurons in the spinal cord and brainstem, white matter atrophy, and partial androgen insensitivity ( Arnold and Merry, 2019 ). Quantitative brain imaging studies of SBMA patients demonstrated white matter alterations in the corticospinal tracts (CST), limbic system ( Kassubek et al, 2007 ; Unrath et al, 2010 ), and cerebellum ( Pieper et al, 2013 ).…”
Section: Polyq Diseases and Juvenile Casesmentioning
confidence: 99%